Emergent information technologies and enabling policies for counter-terrorism (Wiley-Interscience, 2006)
Emergent Information Technologies and Enabling Policies for Counter-Terrorism provides a unique, integrated treatment of cutting-edge counter-terrorism technologies and their corresponding policy options. Featuring contributions from nationally recognized authorities and experts, this book brings together a diverse knowledge base for those charged with protecting our nation from terrorist attacks while preserving our civil liberties.